2023
DOI: 10.1039/d3sc02404k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically assisted morphing of shape shifting polymers

Rui Tang,
Wenli Gao,
Yulin Jia
et al.

Abstract: Morphing in creatures have inspired various synthetic polymer materials that are capable of shape shifting. The morphing of polymers generally relies on stimuli-active (typically heat and light active) units that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The activation stress thresholds of spirolactam in DN elastomers 2 and 3 are similar (3.49 vs 3.82 MPa) and located in strain-hardening regions despite their different activation strain thresholds (275 vs 350%). We conclude that spirolactam is activated during the enthalpic stretching of polymer chains, while the aggregates of PhMz-4OH are destroyed once the entropic stretching of polymer chains happens …”
Section: Resultsmentioning
confidence: 86%
“…The activation stress thresholds of spirolactam in DN elastomers 2 and 3 are similar (3.49 vs 3.82 MPa) and located in strain-hardening regions despite their different activation strain thresholds (275 vs 350%). We conclude that spirolactam is activated during the enthalpic stretching of polymer chains, while the aggregates of PhMz-4OH are destroyed once the entropic stretching of polymer chains happens …”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, guidelines for molecular design to accelerate the thermal reverse reaction of HABI are still unknown and remain a challenge. Accelerating the thermal reverse reaction of HABI could improve the performance of photoinitiators and provide HABI-based self-healing polymers , and photoplastic elastomers , with fast-response capabilities. We found that the radical recombination reaction rate of compound 1 (Scheme b), in which the ortho -carbons of the phenyl groups B and C are linked by an ether bond to form a dibenzo­[ b , f ]­oxepine imidazole scaffold, is more than 100 times faster than that of o -Cl-HABI.…”
mentioning
confidence: 99%